Instilling and Applying Pancasila Values to “Money Wasters” Students - Untara, Bernadinus Krida Estu (Journal of Creativity Student, 2019)
Some university students still doing hedonism things that if they do hedonism continuously, there will be risk case for them, so many university students that are feeling sorry and regret it. Other than that, hedonism thing can make “don’t worry, if there are much money, case closed” mental for all university student. This will be dangerous for our future life, because university students is “agent of change” for future. With Pancasila, author hope that all that values included in Pancasila can make a positive influence for university student to be “frugal”. Other than that, with Pancasila, author hope that hedonisme thing that people do didn’t make Pancasila value be ruined.